HLA inherence as a potential parameter in checkpoint inhibitor-associated autoimmune adverse event assessment - Gandarillas, Sophia; Newland, Elizabeth Schoenberg; Toppmeyer, Deborah; Stephenson, Ryan; Denzin, Lisa; Dasgeb, Bahar (Frontiers in Medicine, 2024)
The success of immunotherapy has made it a lifesaving treatment, but not without side-effects. The risk factors for developing immune-related adverse event (irAE)s in patients who receive immunotherapy are poorly understood, and there is no risk stratifying mechanism for irAEs. It is postulated that oncology patients with preexisting autoimmune diseases are likely to have flares on immunotherapy.1 However, some patients develop de novo autoimmune conditions without a prior history. The literature postulates that HLA inherence may play a role in irAEs however, it remains under-explored. The nine oncology patients, who developed irAEs on immunotherapy, specifically CIs for whom the continuation of treatment was prudent were selected. Of the selected, one had prior history of autoimmune condition. None of the patients had an active autoimmune condition at the time of CI initiation. Their HLA was typed, and the results were cross-referenced with the literature in PubMed and Google search with the corresponding autoimmune condition of each patient. Herein the patients with irAE for whom retrospective HLA-typing revealed inherence of multiple related HLA alleles that may correspond to the autoimmune condition that they had developed on immunotherapy. Inherence of enriched disease-related HLA alleles was shared among patients with the same irAE. These patients developed irAEs including BP, PF/PV, thyroiditis, vitiligo, and hepatitis on immunotherapy. Although some combinations of disease-related HLA were reported in idiopathic autoimmune diseases, a frequently repeated HLA allele combination in our patient population was found to be rarely seen in general population. The authors suggest that an enriched inherence of disease-related HLA alleles may play a role in genetic propensity for development of irAEs in oncology patients on immunotherapy, including CI. Inherence of particular autoimmune disease-related HLA alleles in patients who receive immunotherapy may unmask the corresponding autoimmune disease as the genotype inherence presents with the phenotype of the corresponding condition. It is suggested that enriched linked HLA genotype, which are otherwise rare in general population, may present as the corresponding phenotype of the autoimmune condition. Such clinical presentation, enhanced by immunotherapy, such as CI, can play a role in risk stratifying patients for precision medicine to improve outomes.